Media pembelajaran sebagai solusi untuk meningkatkan pengetahuan dan kemampuan pada siswa - Hasibuan, Rosmaini; Siregar, Samsuddin; Widianingsih, Onyas; Natas Pasaribu, Ahmad Muchlishin (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2024)
The selection of appropriate learning media is proven to have a positive impact on students' knowledge and abilities in the learning process. They were referring to material in learning carried out by sports students as one of the preparations for teachers who must understand refereeing regulations so that the entire learning process can really utilize learning media. This study aims to determine the effect of the application of learning media on remembering the knowledge and ability of volleyball referees. The research method used in this study is quasi-experiment with a pretest and posttest quasi-experimental control group research design. This study involved 30 volleyball referee students who were obtained using cluster random sampling. This research instrument is an instrument that uses a questionnaire on the level of knowledge and ability of volleyball referees, divided into 10 indicators. This questionnaire obtained a reliability of 0.826. The analysis of this data used prerequisite tests (normality test using the Kolmogorov Smirnov test, homogeneity test using the Levin statistical test), and a t-test conducted with the help of SPSS 25 to test the effect on each subject. The results showed that the average score of the experimental volleyball referee group was 216.93 ± 7.75, while the average score of the control volleyball referee knowledge and ability level group was 189.47 ± 7.18, the experimental group was better than the control group.